2011
DOI: 10.3414/me11-02-0002
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Medical Records and EHR in Asia-Pacific Region

Abstract: This survey on the health record background information has yielded the above mentioned results. This information contributes to the planning and evaluation of medical information systems in the Asia-Pacific region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, the adoption rate of EHRs has been low leading to the passage of the Health Information Technology for Economic and Clinical Health (HITECH) Act in 2009; now, adoption in the United States has significantly increased the number of medical practices who use EHRs [9]. Furthermore, the use of EHRs is increasing in both developing and developed countries [9, 10, 11, 12, 13, 14] leading to widespread use of EHRs by nephrologists. In this article, we will review the structure and function of EHRs, its role in early identification and management of CKD patients, and its potential uses in clinical research related to kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, the adoption rate of EHRs has been low leading to the passage of the Health Information Technology for Economic and Clinical Health (HITECH) Act in 2009; now, adoption in the United States has significantly increased the number of medical practices who use EHRs [9]. Furthermore, the use of EHRs is increasing in both developing and developed countries [9, 10, 11, 12, 13, 14] leading to widespread use of EHRs by nephrologists. In this article, we will review the structure and function of EHRs, its role in early identification and management of CKD patients, and its potential uses in clinical research related to kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies highlighted interventions based around software, web-based platforms, or mobile technologies [21, 24, 25, 36, 37, 46]. Specific ICT interventions incorporated elements of automation [28, 30, 44, 49, 52]; data standardization or quality control [17, 22, 24, 3133, 35, 47]; data visualisations or data mapping [21, 35, 37, 38, 44, 45, 49]; and data analysis tools [22, 24, 29, 3941, 46]. Finally, some studies also specifically mentioned measures protecting patient information [17, 33, 36, 38].…”
Section: Resultsmentioning
confidence: 99%
“…A recent international comparative study of the use of electronic medical records (EMR) for research found that the procedures for information governance, levels of adoption, and required time and ease of obtaining consent varied significantly across the countries [14]. Existing systems for collecting and analysing data frequently lack coordination and effective interconnectedness within the departmental and hospital systems, creating challenges in the analysis and interpretation of patient outcomes, particularly as it pertains to a specific population or community [1517]. The ability to provide effective and preventative care management will require a more sophisticated and expansive level of data collection on selected populations that currently outstrips the capacity of most healthcare organizations [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation